Lebensdauer von LED-Baugruppen - Stöger, Fabian (Spektrum der Lichttechnik, 2022)
This work deals with the material degradation of LED package materials and their contribution to degradation of the whole LED device. The occurring failure modes within the LED package are described and predicted by the degradation of the used package materials. Based on these findings approaches for long lifetime LEDs are derived.